OPTIMIZATION OF LIGHTWEIGHT ELECTRIC BUS FRAME DESIGN THROUGH VALUE ENGINEERING APPROACH: A SYSTEMATIC REVIEW AND PARAMETRIC FEASIBILITY ANALYSIS - Artana, I Nyoman; Sumarsono, Danardono Agus; Huda, Mahfudz Al; Adhitya, Mohammad (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Lightweight frame design plays a critical role in improving the efficiency and sustainability of electric buses. This study aims to explore the optimization of electric bus frame design through the application of Value Engineering (VE), using a systematic literature review (SLR) supported by technical simulation references. The review focused on key parameters, including material selection, structural topology, component dimensions, and production costs, analyzed across more than 40 publications from reputable databases over the past decade. Various studies demonstrate that substituting conventional steel with aluminum alloy 6063 can reduce frame weight by up to 30%, while topology optimization based on Finite Element Analysis (FEA) achieves more efficient load distribution and structural integrity. Additionally, shifting from manual to robotic welding methods has shown to enhance production efficiency by approximately 20%. Despite higher initial costs, VE supports long-term benefits by reducing operational costs, improving energy consumption, and aligning with sustainability goals. The findings suggest that integrating VE into the early stages of electric bus frame design offers a strategic pathway toward lighter, safer, and more cost-effective transportation solutions.